Synthesis, characterization and CO2 adsorption performance of a thermosensitive solid amine adsorbent. (May 2019) - Liu, Fenglei; Fu, Wenhao; Chen, Shuixia
Graphical abstract: Highlights: A thermosensitive solid amine adsorbent was fabricated via crosslinking and free radical polymerization reaction. A high temperature had a negative impact on CO2 adsorption because the CO2 /amine groups reaction was exothermic. Moist has growth-promoting effect on CO2 adsorption capacity due to its improving amine utilization efficiency. This thermosensitive solid amine adsorbent could be regenerated at a lower temperature 60 °C. Abstract: A thermosensitive solid amine adsorbent (PNIPAAm@PEIs) was developed by an inverse suspension polymerization of polyethyleneimine (PEI) and ethylene glycol diglycidyl ether (EDGE), followed by further functionalizing the copolymer with N -isopropylacrylamide (NIPAAm) through free radical polymerization reaction. Different characterization techniques were used to analyze the chemical structure and surface functional groups of the adsorbents. The adsorption behavior of CO2 on the adsorbent was evaluated in a fixed-bed adsorption system equipped with gas chromatography. It was found that a high temperature had a negative impact on CO2 adsorption due to the CO2 /amine groups reaction was exothermic. The existence of water had a growth-promoting effect on CO2 adsorption capacity because of its improvement of the amine utilization efficiency. Highest adsorption amount of 3.15 mmol/g for PNIPAAm@PEIs was obtained at 10 °C under wet condition. Moreover, the CO2 adsorption (25 °C) and desorption (60 °C) behavior showed that PNIPAAm@PEIs could desorb CO2 more efficiently at 60 °C than that of polyethyleneimine sphere (PEIs) due to the temperature-responsive property of poly( N -isopropylacrylamide). This study revealed that introduction of thermosensitive poly( N -isopropylacrylamide) into solid amine could effectively reduce the energy consumption when regeneration of adsorbents.